Crabs as snake predators? An observation from southern Italy leading to a comprehensive review - Daniel Jablonski; David Hegner; Francesco Paolo Faraone; Konrad Mebert (Herpetozoa, 2024)
The recent elevation of the Western Grass Snake, Natrix helvetica, from subspecies status prompted an assessment of its natural history and ecological traits compared to closely related species. We report an unusual predation attempt by the freshwater crab Potamon fluviatile on N. helvetica sicula from Sicily, indicating an ecological interaction previously overlooked in this species. The observation suggests that this crab may utilise snakes’ muscle tissue as an additional nutrient source. This predator-prey interaction, although probably rare, adds to the understanding of the dynamics between crabs and snakes, shedding light on their interaction in freshwater habitats. To provide context for our observation and highlight its rarity, we searched through scientific literature and online sources to generate a comprehensive review of the phenomenon that examines the predatory behaviour of crabs on snakes.